Identifying parameters for cart and pole system - Nguyen , Van Dong Hai; Hoang , Ngoc Van; Nguyen , Minh Tam; Nguyen , Thi Yen Tuyet; Nguyen , Phong Luu (Journal of Technical Education Science, 2016)
The aim of this paper is to use genetic algorithm to identify parameters of a nonlinear balancing system. In this case, single-linked inverted pendulum was chosen. With identified parameters of nonlinear model, a LQR controller was designed to prove that parameters were identified well. Results which were operated in Matlab/ Simulink environment showed that identifying process was good.